Diffusion of digital mobile telephony: Are developing countries different? - Petri Rouvinen (The Research Institute of the Finnish Economy (ETLA), 2004)
Factors determining the diffusion of digital mobile telephony across 200 developed and developing countries in the 1990s are studied with the aid of a Gompertz model. The market size and network effects are found to play more important roles in the developing countries; there is also more need for complementing innovations in, for example, financial and payment systems. Even though the developing countries have disadvantages, being late entrants in digital mobile telephony is to their advantage and promotes cross-country convergence. Overall digital technologies are best seen as equalizers, and thus the divide is rather socio-economic or analog than digital. – – Digitaalisen matkaviestinnän leviämiseen vaikuttavia tekijöitä tutkitaan 200 kehittyneen ja kehittyvän maan 1990-lukua koskevalla aineistolla ja Gompertz mallilla. Markkinakoko ja verkostovaikutukset ovat kehittyvissä maissa kehittyneitä tärkeämpiä; niissä on myös enemmän tarvetta täydentäville innovaatioille esimerkiksi rahoitus- ja maksujärjestelmiin liittyen. Vaikka kehittyvät maat ovat monessa mielessä epäedullisessa asemassa ne hyötyvät siitä, että ne ovat tyypillisesti aloittaneet digitaalisen matkaviestinnän käytön kehittyneitä maita myöhemmin, mikä osaltaan tukee maaryhmien lähenemistä. Ylipäätään digitaaliset teknologiat pääsääntöisesti tasoittavat kehittyvien ja kehittyneiden maiden välisiä eroja; niinpä niiden välinen kuilu on pikemminkin sosiaalis-taloudellinen tai analoginen kuin digitaalinen. – matkaviestintä ; teknologinen diffuusio ; Gompertz malli ; kehittyvät maat
Keywords: L96; O30; O10; 330; mobile telephony; technology diffusion; Gompertz model; developing countries; Mobilkommunikation; Räumliche Innovationsdiffusion; Entwicklungsländer